Analisis perhitungan bunga tabungan PPh pasal 4 ayat (2) yang harus dipotong pada nasabah di Bank SulutGo cabang utama - Gombo, Marselino; Warongan, Jessy D. L; Lambey, Robert (Riset Akuntansi dan Portofolio Investasi, 2025)
Article 4, Paragraph (2) Income Tax on interest from savings is one of the tax objects. Every customer who saves at the bank is subject to a tax of 20% on the gross amount of interest received. This research aims to determine how the tax is calculated and to ensure that the tax withholding is in accordance with the applicable regulations. The research method is qualitative descriptive, using interviews and documentation.The research findings indicate that: Firstly, PT Bank SulutGo Main Branch uses a daily balance method for calculating savings interest. This is automatically calculated by the system and directly credited to the customer's account at the end of the month. Secondly, the 20% tax rate imposed on savings interest is in accordance with the applicable tax regulations, without exception, unless there is a division of balance to avoid taxes.